Activists read "Your Paper" in Billy Defrank Center lounge - Sahl, Ted (photographer):::Creator::::::::::::
Two gay male activists sit on a couch reading an edition of "Your Paper," a GLBT publication, in the lounge of the Billy DeFrank Center.